2015
DOI: 10.3109/14767058.2014.994499
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic fragility of red blood cells, lipid peroxidation and Ca2+-ATPase activity of placental homogenates and red blood cell ghosts in salt-loaded pregnant rats

Abstract: Salt-loaded pregnant rats showed, similar to preeclamptic women, an increased level of lipid peroxidation and a lowered Ca(2+)-ATPase activity in placental and red blood cells membranes, as well as an increased osmotic fragility of the red blood cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
3
4
0
Order By: Relevance
“…Table 2 shows the results obtained. Notice that as previously reported (Beauséjour et al, 2003;Rojas et al, 2015), the increase of sodium intake in pregnant rats (SLP) was accompanied by a significant decrease in placental and fetal weight. The presence of Mg-gluconate in the drinking water of control pregnant rats did not produce any significant change in the fetal parameters of the rats.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Table 2 shows the results obtained. Notice that as previously reported (Beauséjour et al, 2003;Rojas et al, 2015), the increase of sodium intake in pregnant rats (SLP) was accompanied by a significant decrease in placental and fetal weight. The presence of Mg-gluconate in the drinking water of control pregnant rats did not produce any significant change in the fetal parameters of the rats.…”
Section: Resultssupporting
confidence: 70%
“…These features have been interpreted as an indication of a decreased placental perfusion in the salt-loaded pregnant rats (Beauséjour et al, 2003;St-Louis et al, 2006). In our laboratory, we have shown that blood plasma, red blood cells ghosts, and placental homogenates of salt-loaded pregnant rats show an increased level of lipid peroxidation, as well as a concomitant, lowered PMCA activity (Rojas et al, 2015) which was previously shown in both red blood cell ghosts and syncytiotrophoblast plasma membranes from preeclamptic pregnant women (Matteo et al, 1998;Abad et al, 2012). Additionally, red blood cells from experimental rats displayed higher osmotic fragility compare to control rats.…”
Section: Introductionmentioning
confidence: 79%
“…PWH have high reactive species production in peripheral immune cells (67,68) and elevated lipid peroxidation products in plasma (69). We and others have previously shown that RBCs are especially susceptible to oxidative damage by lipid peroxidation (32,33,70), resulting in release of hemoglobin (Hb), metHb, free heme, and free iron (71). In this study we also found that PWH who self-report CWP had elevated levels of carbonyl adducts in RBC membranes.…”
Section: Discussionsupporting
confidence: 65%
“…People with HIV have high reactive species production in peripheral immune cells [ 70 , 71 ] and elevated lipid peroxidation products in plasma [ 72 ]. We and others have previously shown that RBCs are especially susceptible to oxidative damage by lipid peroxidation [ 32 , 33 , 73 ], resulting in release of hemoglobin (Hb), metHb, free heme, and free iron [ 74 ]. In this study we also found that HIV positive individuals who self-report CWP had elevated levels of methemoglobin in plasma and carbonyl adducts in RBC membranes.…”
Section: Discussionmentioning
confidence: 99%